Dead end in Norvelt - Gantos, Jack. (New York : Farrar Straus Giroux, 2011)
In the historic town of Norvelt, Pennsylvania, twelve-year-old Jack Gantos spends the summer of 1962 grounded for various offenses until he is assigned to help an elderly neighbor with a most unusual chore involving the newly dead, molten wax, twisted promises, Girl Scout cookies, underage driving, lessons from history, typewriting, and countless bloody noses.
Keywords: Behavior -- Fiction; Old age -- Fiction; Norvelt (Pa.) -- History -- 20th century -- Fiction